Edmodo-Based E-Learning Media for Middle School Students on Sequences and Series - Ani Afifah; Fatkhur Roji (CV. Bimbimbingan Belajar Assyfa, 2024)
This research aims to develop an Edmodo-based e-learning media integrated with Macromedia Flash 08 for middle school students on sequences and series. The development of this media used a 3-D model (Define, Design, Develop) and focused on assessing the resulting product's validity, practicality, and effectiveness. Validation results showed that the developed learning media were highly valid, with a validity score of 4.68 from media experts and 4.62 from material experts. Regarding practicality, this media was deemed easy to use by teachers (score 4.53) and students (score 4.48). The media's effectiveness was also evident in the student learning achievement rate of 95% and the average positive student response rate of 89%. This learning media increased student interest and motivation in learning mathematics and made learning more engaging and interactive. However, there are challenges such as internet connection stability and the time required to access materials through Edmodo and Macromedia Flash. Overall, Edmodo-based e-learning media combined with Macromedia Flash 08 is a suitable alternative to support mathematics learning in the digital age.